Forecasting with instabilities: An application to DSGE models with financial frictions - Roberta Cardani; Alessia Paccagnini; Stefania Villa (University College Dublin, UCD School of Economics, 2015)
This paper examines whether the presence of parameter instabilities in dynamic stochastic general equilibrium (DSGE) models affects their forecasting performance. We apply this analysis to medium-scale DSGE models with and without financial frictions for the US economy. Over the forecast period 2001-2013, the models augmented with financial frictions lead to an improvement in forecasts for inflation and the short term interest rate, while for GDP growth rate the performance depends on the horizon/period. We interpret this finding taking into account parameters instabilities. Fluctuation test shows that models with financial frictions outperform in forecasting inflation but not the GDP growth rate.
Keywords: C11; C13; C32; E37; 330; Bayesian estimation; Forecasting; Financial frictions; Parameter instabilities